American guerrilla the forgotten heroics of Russell W. Volckmann : the man who escaped from Bataan, raised a Filipino army against the Japanese, and became the true "father" of Army Special Forces - Guardia, Mike (Casemate Publishers, 2010)
Escaping to the jungle of north Luzon after General MacArthur pulled out of Bataan, Captain Russell Volckmann refused to surrender. Over the next three years, he raised a 22,000 strong, Filipino army and led a guerrilla war against the Japanese killing over 50,000 enemy soldiers. Had it not been for Volckmann, the Americans would have gone in "blind" during their counter-invasion. Volckmann is established as the progenitor of modern counter-insurgency doctrine and is the "true" father of Army Special Forces, a title that history has erroneously awarded to Colonel Aaron Bank of the ETO. In 1950 Volckmann wrote two Army field manuals: "Operations Against Guerrilla Forces and Organization" and "Conduct of Guerrilla Warfare", though few today realize he was their author. Taking his argument directly to the Army Chief of Staff, he outlined the concept for Army Special Forces - ultimately securing the establishment of the Army's first Green Beret unit, the 10th Special Forces Group.